SEARCH FOR Z(0) DECAYS TO 2 LEPTONS AND A CHARGED-PARTICLE ANTIPARTICLE PAIR - Abreu, P; Adam, W; Adye, T; Agasi, E; Aleksan, R; Alekseev, G; Algeri, A; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Andreazza, A; et al. (1993)
Based on a sample equivalent to 365 000 hadronic Z0 decays, the search in DELPHI data for pairs of leptons accompanied by a pair of charged particles is described. A total of 11 events were found in the electron channel, 9 in the muon channel and 7 in the tau channel. Results on lepton pairs with a radiated photon are also presented. The data from all channels are compatible with the expectations from standard processes. However, one event was found in the tau channel with an unusually high mass of the charged particle pair.